The Effect of the Science, Technology, Engineering, and Mathematics (STEM) Approach on Higher-Order Thinking Skills in Biology Education: A Meta-Analysis - Aji Adrian; Yulmairosa Yulmairosa; Jamila Isdelia (Jurnal Indonesia Pendidikan Profesi Guru, 2026)
Background: The demands of 21st-century education require students to possess higher-order thinking skills (HOTS), which can be developed through innovative instructional approaches, such as STEM (Science, Technology, Engineering, and Mathematics) learning in biology education. Objective: This study aims to analyse and synthesise the effects of the STEM approach on students’ higher-order thinking skills in biology learning. Method: This study employed a meta-analysis design using 20 relevant empirical studies published between 2020 and 2026. Data were analysed using effect size techniques to determine the magnitude of the STEM approach’s influence on students’ HOTS. Results: The findings revealed that the effect sizes ranged from 0.47 to 7.60, with most studies demonstrating large to very large effect sizes. These findings indicate that the STEM approach, particularly when integrated with deep learning strategies, has a strong influence on improving students’ higher-order thinking skills. Conclusion: The study concludes that the STEM approach is effective in biology learning for enhancing students’ analytical, evaluative, critical thinking, and problem-solving abilities. Contribution: This study contributes to the growing body of evidence supporting STEM-based learning as an effective instructional approach for developing higher-order thinking skills and strengthening 21st-century competencies in biology education.